Utilization of Local Culture "Mbolo Weki" For Stunting Prevention in Bima District - Aniharyati, Aniharyati; Hendari, Rini; Nurhaeni, Heni; Utami, Sukandri (International Journal of Scientific Research and Management (IJSRM), 2025)
Stunting is a condition of failure to thrive in children under two years old, due to chronic malnutrition so that the child becomes too short for his age. Children with stunting experience impaired physical growth and brain development, which has a negative impact on the child's health.One of the efforts to prevent stunting is by utilizing local culture. I'm sorry(Bima language), is adeliberation event at night, which is held to prepare for important events such as weddings, circumcisions,thanksgiving and so on in a family of the Mbojo tribe.This study aims to analyze the effectiveness of the interventions carried out. With the research design used is "Pre-Post" in different groups (control and intervention).This study aims to analyze the effectiveness of the intervention carried out. With the research design used is "Pre-Post" in different groups (control and intervention). The data obtained were analyzed using the Wilcoxonstatistical test with a significance limit of p ≤ 0.05. The sampling technique was random proportional to size type. The results of this study indicate that there is a difference in knowledge and attitudes between the control group and the Intervention Group before and after the health education intervention was carried out by utilizing the local culture of mbolo weki for stunting prevention. The difference in knowledge and attitudes after receiving health education intervention by utilizing the local culture of mbolo weki for stunting prevention was greater inthe intervention group compared to the control group. The government wants to establish the Mbolo Weki Stop Stunting Movement Program (Gembos stunting).